Validação da versão brasileira do World Health Organization Disability Assessment Schedule (WHODAS 2.0) para indivíduos com disfunção temporomandibular - Mendes, Luana Maria Ramos (2020)
INTRODUCTION: Temporomandibular Dysfunction (TMD) is a term that involves a series of disorders that affect the temporomandibular joint(TMJ), masticatorymuscles and associated structures. It is a major public health problem,as it is one of the main sources of chronic orofacial pain that interferes with daily activities. There is still no instrument to assess functioning, according to the ICF theoretical-conceptual model in individuals with TMD. Therefore, a validation of theWHODAS 2.0 (World Health Organization Disability Assessment Schedule 2.0) for this population would be of great contribution for both clinical and scientific purposes, which would provide a reliable measure of functioning for this population. OBJECTIVES: To validate the Brazilian version of WHODAS 2.0 for individuals with Temporomandibular Disorders. METHODS: This is a methodological study of validation and evaluation of the psychometric measures of the Brazilian version of WHODAS 2.0 for individuals with TMD. Statistical analysis was performed by calculating Cronbach's alpha coefficient (internal consistency), Spearman correlation (criterion validity), Kruskal-Wallistest, andmultiplecomparisons (Dunn method) (discriminant validity). In addition, to describe the sociodemographic, clinical, functioning and quality of life characteristics of the studied participants, the following descriptive measures were taken: central tendency (mean), dispersion (standard deviation), and relative frequency (%). Hence, the SPSS 20.0 software was used, assuming a significance value of 5%. RESULTS: 100 subjects diagnosed with TMD were evaluated according to the RDC/TMD. The sample was composed mostly of women (78%), with an average ageof 33.68 (± 13.52) years, students (38%) or engaged in some kind of paid work (37%) and never got married (55%). The diagnosis of TMD in the vast majority was of Muscular Disorders (81%). The results of internal consistencyfor the domains ranged from 0.56 to 0.93. WHODAS 2.0 showed a moderate and significant correlation with the disability points of the RDC/TMD and with the WHOQOL-bref domains. In the discriminant validity, significant differences were found in alldomains of WHODAS 2.0 between grade 0and grade III, between grade I and grade III, and between grade II and grade III from the RDC/TMD chronic pain grading. CONCLUSION: The obtained results demonstrate that the instrument is reliable and validfor measuring functioning in individuals with TMD,presenting acceptable psychometric properties for internal consistency, as well as for criterion validity and discriminant validity.